The Nordic Income Equality Model in Health Promotion - Torp, Steffen; Reiersen, Jon (Socialmedicinsk tidskrift, 2020)
We highlight and analyze an important channel for redistribution of income in the Nordic countries, often underemphasized in the scholarly literature that analyze the relationship between income equality and public health. We show how coordinated wage bargaining and solidaristic wage policy lead to wage compression, and thereby to low market income inequality in the Nordic countries. We also show that there are important spillovers between the distribution of wages decided in the labor market and the political support for a universal and comprehensive welfare state. Furthermore, we argue that small differences in income have not only contributed to good public health, but also to good economic performance in the Nordic countries.